Association between cervical length and massive intraoperative bleeding in patients with suspected placenta accreta spectrum combined with placenta previa: A retrospective cohort study - Huang, Fusen; Wang, Jingjie; Xu, Yi; Xiong, Qiuju; Wang, Wenjian; Zhuo, Jia; Xia, Qiuling; Yang, Xiaojuan (Frontiers in Surgery, 2022)
Purpose Abnormal placentation is a spectrum disorder that includes creta, increta, and percreta; the term placenta accreta spectrum (PAS) disorders is used as a broad term to describe all of these conditions. PAS can lead to life-threatening hemorrhage. The predictive value of cervical length (CL) in patients with PAS remains controversial. Thus, this study investigated the relationship between CL and the probability of major bleeding in patients with PAS and placenta previa. Methods This retrospective cohort study was conducted at a comprehensive tertiary hospital in Chongqing, China, between January 2018 and December 2020. The target independent and dependent variables were CL and intraoperative massive bleeding, respectively. The covariates included demographic, clinical, and ultrasound characteristics. Logistic regression was used to explore the association between CL and massive bleeding. Results In total, 317 participants were enrolled, in whom the prevalence of massive bleeding was 41.9% (133/317). The threshold of CL associated with massive bleeding (≥1,000 ml) was 33 mm based on a receiver operating characteristic curve. In the fully adjusted model for each additional unit of CL, the risk of massive bleeding decreased by 7% [95% confidence interval (CI), 0.88–0.98]. The risk of major bleeding was reduced by 44% in patients with a CL greater than 33 mm (95% CI, 0.33–0.97) compared with patients with a CL less than 33 mm. Conclusions CL was negatively associated with massive intraoperative bleeding in patients with PAS combined with placenta previa. When the CL was greater than 33 mm, the risk of bleeding decreased by 44%. Thus, CL can be used as a standalone parameter to identify the risk of massive intraoperative bleeding in patients with suspected PAS.